2018
DOI: 10.1002/arch.21524
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like peptides of the legume pod borer, Maruca vitrata, and their mediation effects on hemolymph trehalose level, larval development, and adult reproduction

Abstract: Insulin-like peptides (ILPs) of insects mediate various physiological processes including hemolymph sugar level, immature growth, female reproduction, and lifespan. In target cells of ILPs, insulin/insulin-like growth factor signaling (IIS) is highly conserved in animals. IIS in the legume pod borer, Maruca vitrata (Lepidoptera: Crambidae), is known to be involved in maintaining hemolymph trehalose levels and promoting larval growth. However, ILPs in M. vitrata have not been reported yet. This study predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(59 reference statements)
3
6
0
Order By: Relevance
“…Trehalose homeostasis is mainly controlled by enzyme activities of TPS for trehalose synthesis and TRE for trehalose degradation (Becker et al, 1996). Silencing TPS can significantly downregulate hemolymph trehalose level, while silencing TRE expression can upregulate its level in M. vitrata (Al Baki et al, 2019a). In our current study, ILP mutants showed upregulated TPS expression but downregulated TRE expression.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Trehalose homeostasis is mainly controlled by enzyme activities of TPS for trehalose synthesis and TRE for trehalose degradation (Becker et al, 1996). Silencing TPS can significantly downregulate hemolymph trehalose level, while silencing TRE expression can upregulate its level in M. vitrata (Al Baki et al, 2019a). In our current study, ILP mutants showed upregulated TPS expression but downregulated TRE expression.…”
Section: Discussionsupporting
confidence: 48%
“…They play important roles in mediating immature growth and adult reproduction (Al Baki et al, 2018a, 2020. Furthermore, their expression patterns are similar among different developmental stages and tissues (Al Baki et al, 2019a). Furthermore, IIS components responding to ILPs are well conserved in M. vitrata (Al Baki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of TPS3 increased 48 h after GSK-3 interference, probably because the structure of TPS3 is different from that of TPS1 and TPS2, so their functions are also different. Al Baki MA et al found that the chyme content of Alpaki was increased after Ilp and InR RNAi (Al Baki et al, 2019), which is consistent with the results of this study (Figures 6A,B), that is, glycogen and glucose are converted into trehalose after dsGSK-3 injection, which leads to an increase in glucose metabolism and maintains the balance of glucose metabolism in insects, which is consistent with previous studies (Mitsumasu et al, 2010;Tang et al, 2012).…”
Section: Discussionsupporting
confidence: 92%